Personal Unique Time Table Generator For Student in UTP - Muhammad Faiz bin Ahmad Fauzi, Muhammad Faiz (Universiti Teknologi Petronas, 2012)
This project is to create a new system that generate unique timetable for students in Universiti Teknologi Petronas which include function for reducing time consumption and automate student manual process during timetabling or find alternative of slot. EasyPHP is use to create dynamic web application including the algorithm. Other than that, this project also aims to improvise the current timetable in term of Human Computer Interaction where better visual design and application of colour are included. As add on, this project can provide backup timetable in various medium such as smartphone, social network and email as both of them are the most gadget and site used by students nowadays. At same time, students can do discussion from the medium aforementioned such as Facebook's group and GoogleGnrup's thread.